PERSEPSI SISWA TENTANG KEROHANIAN ORANG TUA DAN MINAT SISWA PADA MATA PELAJARAN AGAMA - Juwinner Dedy Kasingku; Ady Kosegeran (KOLONI, 2022)
This study is a quantitative study to determine students' perceptions of parents' spirituality measured in terms of reading God's word, morning and evening worship, Sabbath worship, evening prayer requesting prayer, praying and limited to data collected through questionnaires based on respondents' perceptions questionnaires. Students' interest in Adventist Christian subjects was measured in terms of activeness during the learning process. The level of children's perception of the spirituality of their parents is at a high level with a mean of 4.12. Meanwhile, the level of student interest in Adventist Christian subjects was at a high level with a mean of 3.67. there is no significant difference in the level of student interest in Adventist Christian religion. there is no significant difference in the level of student interest in Adventist Christian religion. The difference test using ANOVA as shown in table 4, found (Sig = .662 = 0.05). Thus, this finding accepts H01 which states that there is no difference in the level of student interest in Adventist Christianity and there is no significant correlation between parental spirituality and student interest in Adventist Christian subjects (Sig = 0.88 = 0.05). In the absence of such a significant relationship, H02 which states that there is no significant relationship between parental spirituality and student interest in Adventist Christian subjects is "not rejected". his shows that the spirituality of parents does show a high level but there is no significant relationship with students' interest in learning, this also shows that other factors such as the place where they go to school can make children have a high interest in things. spirituality. Keywords: students’ perception, parents’ spirituality, religious study